The Impact of technical assistance on institutional development - Dong, Yoonjei (KDI School, 2013)
In order to improve the institution of developing countries, many donor countries, including emerging donors, provide official development assistance (ODA) in the form of technical assistance. However, it has been difficult to assess the outcomes of technical assistance with precision, which may frequently be indirect and have long time lags. This paper analyzes evaluation reports and academic papers that attempt to measure the impact of technical assistance and empirically tests the relationship between technical assistance and governance.Based on a cross-sectional times-series analysis, this paper finds that the effectiveness of technical assistance may depend on the country’s initial level of institutional quality. This paper also recommends donor countries to conduct rigorous impact evaluation of technical assistance projects in order to improve their effectiveness
Thesis(Master) -- KDI School: Master of Development Policy, 2013
Keywords: Technical assistance--Developing countries